Association of type 2 diabetes mellitus with incidences of microvascular invasion and survival outcomes in hepatitis B virus-related hepatocellular carcinoma after liver resection: A multicenter study. Issue 1 (January 2022) - Zhang, Xiu-Ping; Chai, Zong-Tao; Feng, Jin-Kai; Zhu, Hui-Min; Zhang, Fan; Hu, Yi-Ren; Zhong, Cheng-Qian; Chen, Zhen-Hua; Wang, Kang; Shi, Jie; Guo, Wei-Xing; Chen, Chao-Shuang; et al.
Abstract: Background: Microvascular invasion (MVI) adversely affects long-term survival in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). This study aimed to examine the association between preoperative type 2 diabetes mellitus (T2DM) with incidences of MVI and prognosis in HBV-related HCC after liver resection (LR). Material and methods: Data of HBV-related HCC patients who underwent LR as an initial therapy from four hospitals in China were retrospectively collected. Clinicopathological factors associated with the incidence of MVI were identified using univariate and multivariate logistic regression analysis. The recurrence-free survival (RFS) and overall survival (OS) curves between different cohorts of patients were generated using the Kaplan-Meier method and compared using the log-rank test. Results: Of 1473 patients who were included, 219 (14.9%) patients had T2DM. Preoperative T2DM, HBV DNA load, antiviral treatment, AFP level, varices, and tumor encapsulation were identified to be independent predictors of the incidence of MVI. Patients with HBV-related HCC and T2DM had a higher incidence of MVI (65.8%) than those without T2DM (55.4%) (P = 0.004). The RFS and OS were significantly worse in patients with T2DM than those without T2DM (median RFS: 11.1 vs 16.7 months; OS: 26.4 vs 42.6 months, both P < 0.001). Equivalent results were obtained in HCC patients with MVI who had or did not have T2DM (median RFS: 10.0 vs 15.9 months; OS: 24.5 vs 37.9 months, both P < 0.001). Conclusions: Preoperative T2DM was an independent risk factor of incidence of MVI. Patients with HBV-related HCC and T2DM had worse prognosis than those without T2DM after LR.